Continuous Spinal Anesthesia for Obstetric Anesthesia and Analgesia - Veličković, Ivan; Pujic, Borislava; Baysinger, Charles W.; Baysinger, Curtis L. (Frontiers in Medicine, 2017)
The widespread use of continuous spinal anesthesia (CSA) in obstetrics has been slow because of the high risk for post-dural puncture headache (PDPH) associated with epidural needles and catheters. New advances in equipment and technique have not significantly overcome this disadvantage. However, CSA offers an alternative to epidural anesthesia in morbidly obese women, women with severe cardiac disease, and patients with prior spinal surgery. It should be strongly considered in parturients who receive an accidental dural puncture with a large bore needle, on the basis of recent work suggesting significant reduction in PDPH when intrathecal catheters are used. Small doses of drug can be administered and extension of labor analgesia for emergency cesarean delivery may occur more rapidly compared to continuous epidural techniques.